Nano drugs delivery system: A novel promise for the treatment of atrial fibrillation - Wang, Zhengjie; Tong, Qi; Li, Tao; Qian, Yongjun (Frontiers in Cardiovascular Medicine, 2022)
Atrial fibrillation (AF) is one of the most common sustained tachyarrhythmias worldwide, and its prevalence is positively correlated with aging. AF not only significantly reduces the quality of life of patients, but also causes a series of complications such as thromboembolism, stroke, and heart failure, increases the average number of hospitalizations of patients, and brings a huge economic burden to patients and society. Traditional drug therapy and ablation have unsatisfactory success rates, high recurrence rates, and the risk of serious complications. Surgical treatment is highly traumatic. The nano drug delivery system has unique physical and chemical properties, and in the application of AF treatment, whether it is used to assist in enhancing the ablation effect or for targeted therapy, it provides a safer, more effective and more economical treatment strategy.